Antarctic governance in a climate changed world - McGee, J; Haward, M (Australian Journal of Maritime & Ocean Affairs, 2019)
The Antarctic Treaty System (ATS) is regarded as one of the more successful cases of international governance. For nearly 60 years, the ATS has provided the basis for peaceful use of the Antarctica and facilitated international cooperation on scientific research onthe continent. The ATS now faces several new challenges largely driven by global environmental change from human activities carried out outside the region. Most prominently, human-induced climate change is impacting the Antarctic cryosphere and marine ecosystems of the Southern Ocean and increasing the scope of human activities in these areas. A key challenge for Antarctic governance will be managing regime interaction between the ATS and the growing number of environmental, resource management and wider regimes operating in the region. Given this institutional complexity, we argue that the concept of an Antarctic regime complex provides useful insights for understanding interaction between the ATS and other institutions operating within the region. Finally, we conclude that the ATS will likely require a new level of institutional resilience in interactingother regimes within the Antarctic regime complex, as it continues to perform a key role in shaping governance of the region.